DEKONTAMINASI BAKTERI Escherichia coli DAN Staphylococcus aureus PADA SARANG BURUNG WALET DENGAN PERLAKUAN PEMANASAN (Decontamination of Escherichia coli and Staphylococcus aureus in Edible Bird´s Nest Using Heat Treatment) - Saimah Saimah; Mirnawati B. Sudarwanto; Hadri Latif (Jurnal Kedokteran Hewan, 2016)
This research was aimed to examine the heating effect at 70 C for 3.5 seconds on Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) decontamination in edible bird´s nest. This study used 40 clean edible bird´s nest samples. Samples were divided into two groups, first group was contaminated with E. coli and second group was contaminated with S. aureus. Each group was divided into two treatments. The first treatment was directly tested for microbiological examination and the second treatment was heating at temperature 70 C for 3.5 seconds prior to microbiological examination. The results showed that both of bacteria E. coli and S. aureus had been destroyed by heating treatment. Heating process at 70 C for 3.5 seconds was effective for decontamination of both E.coli and S.aureus.